Augmented Inhibition from Cannabinoid-Sensitive Interneurons Diminishes CA1 Output after Traumatic Brain Injury - Johnson, Brian N.; Palmer, Chris P.; Bourgeois, Elliot B.; Elkind, Jaclynn A.; Putnam, Brendan J.; Cohen, Akiva S. (Frontiers in Cellular Neuroscience, 2014)
The neurological impairments associated with traumatic brain injury include learning and memory deficits and increased risk of seizures. The hippocampus is critically involved in both of these phenomena and highly susceptible to damage by traumatic brain injury. To examine network activity in the hippocampal CA1 region after lateral fluid percussion injury, we used a combination of voltage sensitive dye, field potential and patch clamp recording in mouse hippocampal brain slices. When the stratum radiatum was stimulated in slices from injured mice we found decreased depolarization in stratum radiatum and increased hyperpolarization in stratum oriens, together with a decrease in the percentage of pyramidal neurons firing stimulus-evoked action potentials. Increased hyperpolarization in stratum oriens persisted when glutamatergic transmission was blocked. However, we found no changes in stratum oriens responses when the alveus was stimulated to directly activate stratum oriens. These results suggest that the increased stratum oriens hyperpolarization evoked by stratum radiatum stimulation was mediated by interneurons that have cell bodies and/or axons in stratum radiatum, and form synapses in stratum pyramidale and stratum oriens. A low concentration (100 nM) of the synthetic cannabinoid WIN55,212-2,restored CA1 output in slices from injured animals. These findings support the hypothesis that increased GABAergic signaling by cannabinoid sensitive interneurons contributes to the reduced CA1 output following traumatic brain injury.